Low serum adiponectin level is associated with central arterial stiffness in patients undergoing peritoneal dialysis - Ti-Kang Chen; Yu-Chien Pan; Chih-Hsien Wang; Jia-Sian Hou; Bang-Gee Hsu (Tzu Chi Medical Journal)
Objective: Adiponectin has antidiabetic, anti-atherosclerotic, and anti-inflammatory functions and protects against vascular damage. Carotid-femoral pulse wave velocity (cfPWV) is a noninvasive method for measuring central artery stiffness, which is known to be associated with cardiovascular disease in peritoneal dialysis (PD) patients. This study was conducted to evaluate the relationship between central arterial stiffness and serum adiponectin levels in PD patients. Materials and Methods: Fasting blood samples were obtained from 60 PD patients, and the cfPWV value was measured using a validated tonometry system. In this study, cfPWV values of >10 m/s were used to define the high arterial stiffness group according to the European Society of Hypertension and the European Society of Cardiology guidelines. Results: Among 60 patients with PD, 19 patients (31.7%) were included in the high arterial stiffness group. When compared to those in the control group, the high arterial stiffness group patients were older (P = 0.029), had longer PD vintage (P = 0.001), higher diastolic blood pressures (P = 0.030), higher fasting glucose (P = 0.014), and lower serum adiponectin levels (P = 0.001). After multivariable logistic regression analysis, serum adiponectin (odds ratio, 0.612; 95% confidence interval: 0.426–0.879; P= 0.008) was identified as an independent predictor of arterial stiffness. The multivariable regression analysis also showed that the adiponectin level (β = −0.408; adjusted R2 change = 0.183; P< 0.001) was negatively associated with cfPWV values in patients undergoing PD. Conclusion: Low serum adiponectin level is an independent marker of arterial stiffness in patients undergoing PD.